The Integration of The Application of Forensic Accounting and Investigation Audit on Fraud: A Literature Study - Farizah Sulong; Padri Achyarsyah; Muhammad Nur; Arni Karina; Kumba Digdowiseiso (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
In reporting a company's financial condition, fraud still frequently occurs, where companies produce false financial reports for their benefit. This fraudulent activity harms various stakeholders, including investors who are deceived by these fabricated financial reports, leading them to invest in such companies. Researchers analyzed the roles of forensic accounting and investigative auditing in addressing and reducing fraud. Qualitative research methods were employed, utilizing literature review techniques. The findings indicate that both forensic accounting and investigative auditing are effective in uncovering fraudulent activities within companies. Furthermore, these two fields are capable of working in tandem, each playing a distinct role in the process of exposing fraudulent activities undertaken by a company